Accelerator-containing electrolytes for bottom-up copper electroplating.

The copper electrodeposition electrolyte, containing cupric ions, aromatic amines, a complexing agent, and specific accelerators, addresses the challenge of void formation in copper interconnects, achieving defect-free copper filling and enhanced deposition quality.

JP2025510877AActive Publication Date: 2025-04-15MACDERMID ENTHONE INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024557104
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-05
Filing Date
2023-04-04
Publication Date
2025-04-15
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

Existing copper electrodeposition solutions struggle to fill etched lines and holes in semiconductor substrates without forming voids or crystalline lines, which increase resistance and can cause breakage of copper conductive wires.

Method used

A copper electrodeposition electrolyte comprising cupric ions, at least two aromatic amines, a complexing agent for cupric ions, and at least one accelerator selected from dithiodiglycolic acid, thioglycolic acid, thiourea, ammonium thiocyanate, thiocyanate, and their combinations, is used for electrochemical copper deposition on conductive substrates.

Benefits of technology

The solution achieves significantly higher accelerator effects, resulting in void-free filling of damascene structures by bottom-up mechanisms, with improved copper deposition quality and faster filling rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510877000001
    Figure 2025510877000001
  • Figure 2025510877000002
    Figure 2025510877000002
  • Figure 2025510877000003
    Figure 2025510877000003
Patent Text Reader

Abstract

The present invention relates to an electrolyte composition for depositing copper on a conductive surface. The composition contains a combination of two aromatic amines, a complexing agent for copper(II) ions, and an accelerator such as dithiodiglycolic acid, thioglycolic acid, thiourea, ammonium thiocyanate, thiocyanic acid, or a combination thereof. The present invention also relates to a process for making copper interconnects, comprising a step of electroplating copper into a cavity with the electrolyte. The electrolyte makes it possible to produce copper interconnects with improved bottom-up effect during the copper-filling electroplating step.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copper electrodeposition solution for electroplating copper onto metal surfaces, which can be used in a process for filling etched lines and holes in semiconductor substrates to fabricate interconnects in integrated circuits. [Background technology]

[0002] The demand for faster circuit speeds and higher circuit density for semiconductor integrated circuit (IC) devices such as computer chips requires smaller feature sizes. The trend toward smaller device sizes and increased circuit density necessitates a reduction in the dimensions and increased density of interconnect features. Interconnect features are features such as vias or trenches formed in a dielectric substrate that is then filled with a metal, typically copper, to provide a conductive interconnect. Copper is the metal of choice because copper metallization allows for smaller features and uses less energy to pass electricity, making it better conductor of electricity than any metal except silver. In damascene processing, the interconnect features of semiconductor IC devices are metallized using electrolytic copper deposition.

[0003] Recently, new copper plating processes are being evaluated to address the demands of both miniaturization and integration in advanced portable electronic products.

[0004] Miniaturization of devices such as high-power computer chips with high storage density and low dissipation also requires smaller dimensions for interconnects such as through silicon vias (TSVs). Hence, technology semiconductor device fabrication nodes below 30 nm are being developed for chip manufacturing.

[0005] Interconnects form a network of conductive copper metal to connect various electrical devices within a dielectric material, typically silicon oxide. Fabrication of interconnects involves etching trenches in a dielectric material layer and etching blind vias that are used to connect two different dielectric material layers. The formed cavities are then filled with copper.

[0006] There is a need to increase production rates without any deleterious defects, particularly without voids or habit lines in the copper interconnects that tend to increase resistance or even cause breakage of the copper conductive lines.

[0007] It has been found that many of the known electrolytes cannot be used on an industrial scale to fill trenches and vias with small opening dimensions and / or large depth dimensions, i.e., defects in the copper volume, including voids, may form during copper filling with conventional acid copper ion baths.

[0008] During interconnect manufacturing, patterns are typically filled with copper using copper plating techniques to form conductive lines. Copper electroplating may also be performed when a very thin copper layer (called a copper seed layer) is required on the pattern surface prior to the copper filling step. However, electrolytes that work for copper seed plating generally cannot be adapted for copper fill plating.

[0009] Solutions containing bipyridine and pyridine are described, for example, in U.S. Patent No. 9,133,560 to Daviot et al., the subject matter of which is incorporated herein by reference in its entirety. These solutions were designed to create copper seed layers on substrates with high resistivity. However, it was found that the aqueous copper(II) ion solutions described therein could not be used to fill trenches with copper, in particular because the copper plating rate is very slow.

[0010] There remains a need in the art for improved copper electrodeposition compositions that can avoid deleterious defects in copper interconnects, particularly voids or habit lines that tend to increase resistance or even cause fracture.

[0011] Additionally, there remains a need in the art for electrolytic plating solutions and electrodeposition methods for defect-free copper filling of recessed features via a bottom-up fill mechanism. Summary of the Invention

[0012] According to a first aspect, the present invention relates to an electrolyte for copper electrodeposition comprising, in an aqueous solution, cupric ions, at least two aromatic amines, and a complexing agent for the cupric ions, and at least one accelerator selected from the group consisting of dithiodiglycolic acid, thioglycolic acid, thiourea, ammonium thiocyanate, thiocyanic acid, and combinations thereof.

[0013] According to a second aspect, the present invention provides a process for electrochemical copper deposition onto a substrate comprising at least one exposed conductive surface, the process comprising: - contacting the conductive exposed surface with the copper electrodeposition electrolyte of the present invention; - polarizing the exposed conductive surface with a cathodic current to allow electrodeposition of copper onto the exposed conductive surface for a time sufficient to form a void- and other defect-free copper deposit on the exposed conductive surface; Including, relating to a process.

[0014] Surprisingly, it has been found that the use of dithiodiglycolic acid, thioglycolic acid, thiourea, and thiocyanic acid in the electrolyte results in accelerator effects that are significantly higher than those observed using prior art accelerators such as thiodiglycolic acid, which is a key phenomenon for void-free filling of damascene structures by bottom-up mechanisms.

[0015] In one embodiment, the present invention generally relates to an electrolyte for the electrodeposition of copper onto a conductive substrate, the electrolyte having a pH of 8.5 to 9.5, the electrolyte comprising, in aqueous solution, -0.4 to 50 mM copper(II) ions, - 0.4 to 50 mM of a mixture consisting of a first aromatic amine, a second aromatic amine, and a complexing agent for copper(II) ions; at least one accelerator selected from the group consisting of dithiodiglycolic acid, thioglycolic acid, thiourea, ammonium thiocyanate, thiocyanic acid, and combinations thereof; The present invention relates to an electrolyte, comprising: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present inventors have surprisingly discovered that the addition of certain molecules to copper electrodeposition compositions can improve the quality of bottom-up fill by promoting copper deposition.

[0017] As used herein, the term "accelerator" refers to an organic molecule selected from the group consisting of dithiodiglycolic acid, thioglycolic acid, thiourea, ammonium thiocyanate, and thiocyanic acid. According to certain embodiments, the accelerator improves the quality of the copper deposit in the cavity when the electrolyte is used to fill the cavity via an electrochemical process.

[0018] As used herein, the term "electrodeposition" refers to a method that makes it possible to cover the surface of a substrate with a metallic or organometallic coating, which is electrically polarized and placed in contact with a liquid (called electrolyte) containing the precursors of said metallic or organometallic coating to form said coating. Electrodeposition is carried out, for example, by passing an electric current between the substrate to be coated, which constitutes one electrode (the cathode in the case of metallic coatings) and a second electrode (the anode), optionally in the presence of a reference electrode, in a bath containing a source of precursors of the coating material (for example metal ions in the case of metallic coatings) and, optionally, various agents intended to improve the properties of the coating formed (uniformity and fineness of the deposit, resistance, etc.). By international convention, the currents and voltages applied to the substrate in question, i.e. the cathode of the electrochemical circuit, are negative. Throughout this specification, when these currents and voltages are referred to in positive values, it is implicit that this value represents the absolute value of said current or said voltage.

[0019] As used herein, the term "electrolyte" refers to a liquid containing the precursors of the metal coating used in the electrodeposition process defined above.

[0020] As used herein, the term "opening dimension" of a pattern such as a via or trench refers to the average diameter or width of a pattern previously cut into a dielectric substrate and covered with a metal seed layer, the average diameter being measured at the pattern opening. These dimensions are measured at the surface of the dielectric material, since the average diameter at the bottom of a trench or the average diameter at the bottom of a blind via may differ from the opening dimension, especially if the pattern walls are not perpendicular to the substrate surface.

[0021] As used herein, the term "continuous filling" refers to any void-free copper mass obtained by optimal filling of the entire empty volume of a hollow pattern (also called a cavity or recessed feature) etched in a dielectric substrate. According to the present invention, optimal filling is obtained from the bottom to the opening of the pattern ("bottom-up"). In the prior art, holes or voids ("sidewall voids") may be observed in the copper deposit between the sidewall of the pattern and the copper deposit. Voids equidistant from the sidewall of the pattern in the form of holes or lines ("seams") may also be observed, because generally the copper growth rate at the bottom of the pattern may be slower than the copper growth rate at the sidewall and opening of the pattern. These voids can be quantified on a cross-section of the copper deposit observed by transmission electron microscopy (TEM) at a magnification of 100,000 to 150,000. The continuous copper deposit of the present invention preferably has an average volume percentage of voids of less than 10% by volume, preferably 5% by volume or less. The average void fraction is preferably 0% by volume. The voids may be located in the copper deposit itself. In some cases, such voids form in the upper zone of the cavity because the copper growth rate in the open zone of the pattern is faster than in the bottom zone of the pattern.

[0022] As used herein, the term "about" refers to a measurable value, such as a parameter, amount, duration, etc., and is meant to include no more than + / -15% variation, preferably no more than + / -10% variation, more preferably no more than + / -5% variation, even more preferably no more than + / -1% variation, and even more preferably no more than + / -0.1% variation of and from the specifically recited value, so long as such variations are appropriate to practice the invention described herein. It is further to be understood that the value to which the modifier "about" refers is itself specifically disclosed herein.

[0023] As used herein, spatially relative terms such as "beneath," "below," "lower," "above," "upper," and the like, are used for ease of description to describe the relationship of one element or feature to another element(s) or feature(s) as shown in the figures. Spatially relative terms may be intended to encompass different orientations of the device in use or operation in addition to the orientation depicted in the figures. For example, if a device in a figure is turned over, an element described as "below" or "below" the other element or feature would then be oriented "above" the other element or feature. Thus, the exemplary term "below" can encompass both an upward and downward orientation. The device may be otherwise oriented (rotated 90 degrees or at other orientations) and the spatially relative descriptors may be interpreted accordingly and used herein. It will be further understood that the terms "front" and "back" are not intended to be limiting, and are intended to be interchangeable where appropriate.

[0024] As used herein, "substantially free" or "essentially free" with respect to a particular element or compound means that, unless otherwise defined above, the given element or compound is not detectable by conventional analytical means well known to those skilled in the art of metal plating for bath analysis. Such methods typically include atomic absorption spectroscopy, titration, UV-Vis spectroscopy, secondary ion mass spectroscopy, and other commonly available analytical methods.

[0025] As used herein, the terms "comprises" and / or "comprising" specify the presence of stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. As used herein, the term "between ... and ..." excludes a cut-off value, but the term "from ... to ..." includes the lower and upper recited limits.

[0026] In a first embodiment, the present invention generally relates to an electrolyte having a pH of 8.5 to 9.5 for the electrodeposition of copper on a metal substrate, the electrolyte comprising, in aqueous solution, -0.4 to 50 mM copper(II) ions, - 0.4 to 50 mM of a mixture consisting of a first aromatic amine, a second aromatic amine, and a complexing agent for copper(II) ions; at least one accelerator selected from the group consisting of dithiodiglycolic acid, thioglycolic acid, thiourea, ammonium thiocyanate, thiocyanic acid, and combinations thereof; The present invention relates to an electrolyte, comprising:

[0027] The complexation constant (constant K) of the complex consisting of copper(II) ions and a complexing agent differs by more than 10-fold, preferably more than 100-fold, from the complexation constant of copper(II) complexed with a ligand selected from the group consisting of a first aromatic amine, a second aromatic amine, and mixtures thereof.

[0028] The copper ions are preferably in the form of a complex with the first aromatic amine, the second aromatic amine, and a complexing agent.

[0029] The electrolyte comprises at least one first copper(II) ion complex selected from the group consisting of: - a complex of copper(II) ions with a first aromatic amine and a second aromatic amine, a complex of copper(II) ions with a first aromatic amine in combination with a complex of copper(II) ions with a second aromatic amine, a complex of copper(II) ions with a first aromatic amine and a complex of copper(II) ions with a first aromatic amine and a second aromatic amine; - a complex of copper(II) ions with a second aromatic amine, and a complex of copper(II) ions with a first aromatic amine and a second aromatic amine; and - complexes of copper(II) ions with 2,2'-bipyridine, complexes of copper(II) ions with a second aromatic amine, and combinations of complexes of copper(II) ions with a first aromatic amine and a second aromatic amine.

[0030] The electrolyte preferably comprises at least one second copper(II) ion complex comprising a complexing agent as described herein.

[0031] The complex of copper(II) ion with the complexing agent may have a logarithmic complexation constant (logK) greater than 7.

[0032] The molar ratio between the first aromatic amine concentration and the second aromatic amine concentration may be 1 / 2 to 2 / 1, more preferably 4 / 5 to 6 / 5, and the molar ratio between the first amine concentration and the complexing agent concentration may be 1 / 4 to 4 / 1, for example 1 / 3 to 3 / 1, or 1 / 2 to 2 / 1±10%.

[0033] The complex of copper(II) ion can comprise the first aromatic amine alone, the second aromatic amine alone, or both aromatic amines. In the electrolyte solution, the molar concentration of the complex of copper(II) ion comprising the first aromatic amine and the second aromatic amine is preferably higher than the molar concentration of the copper complex comprising the first aromatic amine and higher than the molar concentration of the copper complex comprising the second aromatic amine. More preferably, the electrolyte does not contain the copper complex comprising only the first aromatic amine and does not contain the copper complex comprising only the second aromatic amine.

[0034] In one preferred embodiment, the first amine can be 2,2'-bipyridine and the second amine can be imidazole.

[0035] Generally, the electrodeposition composition according to the present invention contains cupric ions, Cu 2+ The copper(II) ion source preferably comprises a copper(II) salt, such as copper(II) sulfate, a copper alkylsulfonate, such as copper methanesulfonate, a copper halide, such as copper(II) chloride, copper(II) nitrate, copper(II) citrate, copper(II) oxide, copper(II) carbonate, or copper(II) acetate. In one embodiment, the copper(II) ion source is copper(II) sulfate, more preferably copper(II) sulfate pentahydrate.

[0036] According to a particular feature, the copper(II) ions in complex form are present in the electrodeposition composition in a concentration between 0.4 and 50 mM, preferably between 0.4 and 40 mM, for example between 1.0 and 25 mM, 4.0 and 15 mM.

[0037] The electrolyte advantageously comprises a first complex of copper(II) ions comprising one 2,2'-bipyridine ligand and one imidazole ligand, and a second complex of copper(II) ions and a complexing agent for copper.

[0038] In the electrolyte, the molar ratio between the first complex of copper (II) and the second complex of copper (II) can be advantageously selected as a function of the chemical formula of the complexing agent and the pattern dimensions (such as the opening dimensions and depth). The molar ratio between the first complex of copper (II) and the second complex of copper (II) can be 0.1 to 4.0, for example 0.2 to 3.0, preferably 0.5 to 1.5.

[0039] The ratio between the molar concentration of 2,2'-bipyridine and the molar concentration of imidazole is preferably 1:2 to 2:1, more preferably 4:5 to 6:5, and even more preferably 0.95 to 1.05.

[0040] The ratio of the molar concentration of the complexing agent to the molar concentration of copper(II) ions is preferably 0.15 to 6.0, more preferably 0.2 to 4.0 or 0.3 to 2.5, for example, 0.5 to 2.0.

[0041] The electrolyte of the present invention also includes at least one accelerator selected from the group consisting of dithiodiglycolic acid, thioglycolic acid, thiourea, ammonium thiocyanate, thiocyanic acid, and combinations thereof. In one embodiment, the electrolyte is at least substantially free of thiodiglycolic acid.

[0042] The concentration of the at least one accelerator may be between 0.05 ppm and 200 ppm, advantageously between 0.1 ppm and 20 ppm, depending on the accelerator selected.

[0043] The accelerators used in accordance with the present invention can provide improved acceleration effects when used at mass or molar concentrations equal to or less than the mass concentrations of accelerators such as thiodiglycolic acid used in prior art compositions such as those described in U.S. Patent No. 10,883,185, the entire subject matter of which is incorporated herein by reference. "Improved acceleration effects" means a lower percentage of voids in the copper deposit or a faster filling rate of cavities compared to the use of prior art accelerators.

[0044] Without being bound by theory, it is believed that the reason why the accelerating effect of the compounds described herein is greater than that of thiodiglycolic acid is due to the greater mass percent of sulfur in the compounds. In an alkaline environment, it has been observed that species with accelerating capabilities that contain a higher mass percent of sulfur (of the total compound mass) have better bottom-up effects. This trend is not observed in acid copper electroplating. In one embodiment, the accelerator is dithiodiglycolic acid, which is preferably used at a concentration in the range of 2 ppm to 20 ppm, more preferably 5 ppm to 15 ppm.

[0045] In one embodiment, the accelerator is thioglycolic acid, which is preferably used at a concentration in the range of 0.1 to 20 ppm, more preferably 1 ppm to 10 ppm.

[0046] In one embodiment, the accelerator is thiourea, which is preferably used at a concentration in the range of 0.01 to 5 ppm, more preferably 0.1 to 2 ppm.

[0047] In one embodiment, the accelerator is ammonium thiocyanate, which is preferably used at a concentration in the range of 0.01 to 5 ppm, more preferably 0.1 ppm to 2 ppm.

[0048] In one embodiment, the accelerator is thiocyanic acid, which is preferably used at a concentration in the range of 0.01 to 5 ppm, more preferably 0.1 ppm to 2 ppm.

[0049] In one embodiment, the present invention also provides an electrolyte for the electrodeposition of copper onto a metal substrate, having a pH of 8.5 to 9.5, comprising in an aqueous solution: - 0.4 to 50 mM, for example 0.4 to 40 mM, of copper(II) ions; a mixture of 2,2'-bipyridine and imidazole, in which the ratio between the molar concentration of copper(II) ions and the molar concentration of the mixture of the second aromatic amine is preferably 1 / 5 to 10 / 1, for example 1 / 4 to 5 / 1, 1 / 3 to 3 / 1, 1 / 2 to 2 / 1, or 2 / 3 to 1 / 1, from 0.8 to 80 mM; - a complexing agent for copper(II) ions, which preferably forms, preferably in the electrolyte, a complex with copper(II) ions having a logarithmic complexation constant (logK) higher than 7. -0.05 to 200 mg / L (ppm) of at least one accelerator as described herein; Also of interest is an electrolyte having a pH of 8.5 to 9.5.

[0050] In a particular embodiment of this electrolyte, the ratio between the molar concentration of copper(II) ions and the molar concentration of the mixture of imidazole and 2,2'-bipyridine is between 1 / 4 and 2 / 1.

[0051] The features described herein apply, where appropriate, to any of the aforementioned electrolytes.

[0052] The complexing agent for copper(II) that is part of the electrolyte of the invention or part of the process of the invention for preparing the electrolyte can be selected from the group consisting of citric acid, tartaric acid, phenanthroline, ethylenediaminetetraacetic acid (EDTA), N-(hydroxyethyl)-ethylenediaminetriacetic acid (HEDTA), ethylenediamine, 1,6-diamino-cyclohexane, diethylene-triamine, triethylene-tetramine, N,N,N,N-tetramethyl-ethylene-diamine, N,N-bis(2-hydroxyethyl)ethylenediamine, N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, glycine, 2-amino-ethyl-phosphonic acid, salicylic acid, salicylhydroxamic acid, catechol, 1,2-dihydroxybenzene-4-sulfonic acid, acetylacetone, acetylacetonate, dimethylglyoxime, and 1,3-diamino-propane. The complexing agent, when complexed with copper, can be used in either its acidic or basic form.

[0053] In one particular embodiment, the complexing agent is ethylenediamine.

[0054] In another particular embodiment, the complexing agent is tartrate.

[0055] The electrolyte of the present invention may advantageously be free of polymeric inhibitors such as polyethylene glycol. Furthermore, in the past, a chloride ion source was generally added to the electrolyte to act synergistically with the polymeric inhibitor. However, in the context of the present invention, it has been found that adding chloride ions is not necessary to ensure the effectiveness of the solution. Thus, the electrolyte of the present invention preferably contains less than 50 ppm of chloride ions. More preferably, the electrolyte is at least substantially free of chloride ions.

[0056] While surfactants were typically required in prior art electrolytes to improve the wettability of the surface of the barrier material to be coated with copper, in accordance with the present invention, it is not necessary to incorporate a surfactant into the electrolyte, and thus the electrolyte of the present invention may be substantially free of any surfactant or wetting agent.

[0057] The electrolyte may include levelers and / or brighteners as are known in the art, however, the use of levelers and / or brighteners is not required and good results can be obtained in the absence of levelers and / or brighteners.

[0058] The pH of the electrolyte is preferably selected to be greater than 8.5. Prior art electrolytes used to fill the cavities are generally H + This is all the more surprising since the presence of ions ensures sufficient conductivity of the solution, which in turn has a much lower pH to obtain adequate reaction rates. The pH of the electrolyte of the present invention is preferably 9.0-9.5, even more preferably 9.2±10%. The pH of the electrolyte can be adjusted to the desired range using one or more pH adjusting compounds, including, for example, tetra-alkylammonium salts, such as tetra-methylammonium salts or tetra-ethylammonium salts. In one embodiment, the pH adjuster includes tetramethylammonium hydroxide or tetraethylammonium hydroxide.

[0059] According to a particular embodiment, the concentration of copper(II) ions is between 0.4 and 50 mM, for example between 0.4 and 40 mM, the concentration of 2,2'-bipyridine is between 0.4 and 40 mM, and the concentration of the complexing agent is between 1 and 100 mM.

[0060] When the complexing agent is ethylenediamine, the concentration of copper(II) ions may be 4 to 20 mM, the concentration of the mixture consisting of 2,2'-bipyridine and imidazole may be 5 to 20 mM, and the concentration of the complexing agent may be 1 to 60 mM.

[0061] When the complexing agent is tartrate ions, the molar concentration of copper(II) ions may be 4-20 mM, the molar concentration of the 2,2'-bipyridine and imidazole mixture may be 5-20 mM, and the molar concentration of the complexing agent for copper(II) ions may be 3-50 mM.

[0062] In the electrolyte, the first aromatic amine concentration (for example, 2,2'-bipyridine concentration) is preferably 0.05 to 1 molar equivalent of the copper(II) ion concentration, more preferably 0.1 to 0.8 molar equivalent, more preferably 0.4 to 0.7 molar equivalent.

[0063] In the electrolytic solution, the second aromatic amine concentration (for example, imidazole concentration) is preferably 0.05 to 1 molar equivalent of the copper(II) ion concentration, more preferably 0.1 to 0.8 molar equivalent, more preferably 0.4 to 0.7 molar equivalent.

[0064] The electrolyte is - can be obtained by mixing a first solution containing a first copper(II) ion complex with a second solution containing a second copper(II) ion complex, the first solution being obtained by mixing copper(II) ions, 2,2'-bipyridine, and imidazole, the molar ratio between the 2,2'-bipyridine concentration and the imidazole concentration being in the range of 4 / 1 to 1 / 4; The second solution can be obtained by mixing copper(II) ions with a complexing molecule.

[0065] The concentration of the complexing molecule in the second solution may be 0.15 to 6.0 molar equivalents of the concentration of copper(II) ions in the second solution. The ratio between the molar concentration of copper(II) ions and the molar concentration resulting from the sum of the imidazole molar concentration and the 2,2'-bipyridine molar concentration may be 1 / 5 to 10 / 1 in the first solution.

[0066] The mixing of the first solution and the second solution can be carried out with the volume ratio between the second solution and the first solution being selected to be 5% to 35% by volume, more preferably 10% to 25% by volume.

[0067] The present invention also relates to a process for preparing one of the electrolytes described above.

[0068] Such a process may include the steps of preparing a first solution of a copper(II) complex with 2,2'-bipyridine and imidazole; preparing a second solution of a complex of copper(II) with a complexing agent for copper(II) ions that forms a complex with the copper(II) ions with a logarithmic complexing constant (logK) higher than 7; mixing the first and second solutions in a specific volume ratio; and obtaining an electrolyte containing at least two complexes: a complex of copper(II) with 2,2'-bipyridine and imidazole, and a complex of copper(II) with the complexing agent.

[0069] Another process may include preparing a first solution containing copper(II) ions, a first aromatic amine, and a second aromatic amine to advantageously prepare a complex between the copper(II) ions and the first aromatic amine and / or the second aromatic amine, preparing a second solution containing copper(II) ions and a complexing agent to advantageously prepare a complex between the copper(II) ions and the complexing agent, and mixing the first solution and the second solution.

[0070] In the first solution, the molar concentration of copper(II) ions is preferably 0.3 to 60 mM or 0.8 to 50 mM, preferably 1 to 10 mM, and more preferably 3 to 9 mM.

[0071] In the first solution, the concentration of the first aromatic amine (e.g., 2,2'-bipyridine concentration) and the molar concentration of copper(II) are preferably equal to the concentration of the second aromatic amine (e.g., imidazole concentration) within a possible variation range of ±10%.

[0072] The pH of the first solution may be optionally adjusted using a base or acid known to those skilled in the art after mixing the aromatic amine with the copper(II) ions. The pH adjuster may be, for example, sulfuric acid or a tetraalkylammonium salt, such as a tetramethylammonium salt or a tetraethylammonium salt (e.g., tetramethylammonium hydroxide or tetraethylammonium hydroxide). The first solution may have a pH value of 8 to 10, for example 8.85 to 9.25.

[0073] The pH of the first solution, once adjusted, may optionally be stabilized in the aforementioned pH ranges by buffering agents known to those of skill in the art.

[0074] In the second solution, the molar concentration of copper(II) ions is preferably 30 to 100 mM or 40 to 80 mM, and preferably 60 to 70 mM.

[0075] In the second solution, the concentration of the complexing agent is generally selected in relation to the concentration of copper(II) in the electrolyte in order to form a substantial amount of copper complex with the complexing agent, and the concentration of the complexing agent is preferably 0.5 to 3 molar equivalents of the concentration of copper(II) ions.

[0076] When the complexing agent is a tartrate, the concentration of the complexing agent is 0.5 to 2 molar equivalents of the concentration of copper(II) ions, more preferably 0.65 to 1.25 molar equivalents, more preferably 0.75 to 1.15 molar equivalents, and even more preferably 0.95 to 1.05 molar equivalents. The pH of the second solution may optionally be adjusted using a base or acid known to those skilled in the art after mixing the aromatic amine with the copper(II) ions.

[0077] The second solution may contain a pH adjuster to have a pH value of 7 to 11. It is preferable to adjust the pH to form a complex between the copper ions and the complexing agent.

[0078] The pH of the second solution, once adjusted, may optionally be stabilized in the aforementioned pH ranges by buffering agents known to those of skill in the art.

[0079] The volume ratio between the second solution and the first solution may be 5% to 35% by volume, more preferably 10% to 25% by volume.

[0080] Additional ingredients may be incorporated into the first solution and / or the second solution prior to mixing the two.

[0081] Alternatively, the additional component may be added in a further step following the step of mixing the first and second solutions.

[0082] Although there is no limit in principle to the solvent (as long as it sufficiently solubilizes the active species of the solution and does not interfere with electrodeposition), water is preferred as the solvent for the electrolyte, the first solution and the second solution. According to one embodiment, the solvent essentially comprises water, i.e., it comprises more than 90% by volume of water.

[0083] The first solution and the second solution can be prepared by dissolving a salt selected from the group consisting of copper(II) sulfate, copper(II) chloride, copper(II) nitrate, and copper(II) acetate, or a hydrate thereof, preferably copper(II) sulfate, more preferably copper(II) sulfate pentahydrate, in a solvent.

[0084] The present invention also provides a process for electrochemical copper deposition onto a substrate comprising at least one exposed conductive surface, the process comprising: - contacting the exposed conductive surface with an electrolyte as described above; - polarizing the exposed conductive surface with a cathodic current to allow electrodeposition of copper onto the exposed conductive surface for a time sufficient to form a copper deposit; Including, relating to a process.

[0085] The cavities (also known as patterns) may have an average diameter or width at their opening of 10-30 nm and a depth of 1a-150 micrometers.

[0086] In one embodiment, the process of the present invention is useful for filling patterns cut into a dielectric substrate, the patterns having dimensions less than 45 nm, preferably less than 25 nm, and a form factor greater than 2:1, preferably greater than 3:1.

[0087] In a preferred embodiment, the patterns have opening dimensions less than 25 nm and a form factor greater than 3:1.

[0088] The process may be an electrochemical process for copper filling of a pattern cut into a dielectric substrate and having at least one exposed surface of a metal seed layer, the pattern having an opening dimension of less than 45 nm and a form factor greater than 2, the process comprising: - contacting the exposed surface with one of the electrolytes described herein; - polarizing the exposed surfaces with a cathodic current to allow electrodeposition of copper onto the exposed surfaces for a time sufficient to completely fill the pattern with a void-free copper deposit; Includes.

[0089] All the features described with respect to the electrolyte of the present invention and the process for preparing the electrolyte apply to the electrodeposition process.

[0090] The electrolyte is used by applying an electric current. It is not shown in an electroless process and for this reason does not contain a reducing agent for copper(II) oxide such as dimethylamine borane or hypophosphorous acid.

[0091] The electrochemical process of the present invention has the advantage that it provides copper loading rates that are at least two or at least three times faster than those obtained in identical electrochemical processes except that the electrolyte does not contain a complex of copper(II) ions with the complexing agent described herein.

[0092] In this embodiment, the patterns preferably have opening dimensions less than 25 nm and a shape factor greater than three.

[0093] The copper fill rate depends on the time required to fill the entire volume of a trench or via. The copper fill rate is the percentage of the volume of a pattern cavity that is filled with copper at the end of a given time, e.g., 1 minute or 3 minutes. The copper fill rate can be expressed as the time required to fill the entire volume of a given pattern cavity.

[0094] The present invention also describes a semiconductor manufacturing process similar to a copper damascene system or a copper dual damascene system.

[0095] The first main step involves etching the dielectric substrate. The architecture is made up of a combination of the aforementioned patterns, which can be trenches and vias. A diffusion barrier layer is then placed on the free surface of the dielectric substrate, including the etched patterns, to prevent the subsequently applied copper layer from diffusing into the junctions of the substrate.

[0096] The electrochemical deposition process of the present invention can include forming a thin metal seed layer made of copper (Cu), cobalt (Co), or ruthenium (Ru) before the copper filling step. The metal seed layer can include at least two materials selected from the group consisting of copper (Cu), cobalt (Co), or ruthenium (Ru). In a particular embodiment, the metal seed layer includes a ruthenium layer and a copper layer. In another embodiment, the metal seed layer includes a cobalt layer and a copper layer, and the cobalt layer is laminated on the diffusion barrier layer.

[0097] This thin metal seed layer can be deposited on the diffusion barrier layer using techniques known to those skilled in the art, such as chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD), electroless or electrochemical deposition.

[0098] Thus, the process of the present invention can include forming a metal seed layer using chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD), electroless deposition, or electrochemical deposition, provided that both the electroless deposition and the electrolytic deposition use a different electrolyte than that described with respect to the first embodiment of the present invention.

[0099] In one preferred embodiment of the present invention, the metal seed layer is formed via a PVD route.

[0100] The metal seed layer preferably has a thickness of 0.5 to 20 nm, preferably 1 to 10 nm, for example 2 to 5 nm. Such thickness values ​​are preferably measured on the inner walls of the pattern. In fact, the metal seed layer may have different thickness values ​​on the dielectric substrate field at the pattern opening, and at the pattern sidewalls and at the pattern bottom.

[0101] The diffusion barrier layer may include at least one material selected from the group consisting of tantalum (Ta), titanium (Ti), tantalum nitride (TaN), titanium nitride (TiN), manganese (Mn), and tungsten (W). The thickness of the diffusion barrier layer is typically 0.5-20 nm. The layer may be deposited using techniques known to those skilled in the art, such as chemical vapor deposition (CVD), physical vapor deposition (PVD), or atomic layer deposition (ALD). The diffusion barrier layer may be formed of two layers, each layer being composed of one of the materials disclosed above.

[0102] According to an embodiment of the invention, the dielectric substrate is successively covered on the pattern sidewalls, on the pattern bottom and on the dielectric substrate field with at least two layers of two different materials forming a copper diffusion barrier as disclosed herein above and with a conductive layer as described above.

[0103] The method of the invention allows copper to be deposited in patterns with small opening dimensions, in particular in trenches with very small widths. The opening dimensions of the pattern may therefore be less than the upper limit corresponding to a technology node selected from the group consisting of 45 nm, 40 nm, 35 nm, 30 nm, 25 nm, 20 nm, 15 nm and 10 nm. The opening dimensions of the pattern may be selected in the group consisting of 45 nm, 32 nm, 22 nm, 14 nm, 10 nm, 7 nm and 5 nm. The pattern preferably has an opening dimension of 5 nm or more.

[0104] The shape factor, expressed as the ratio between the pattern depth and the opening size, may vary from 2:1 to 20:1, for example from 3:1 to 10:1. The method according to the invention advantageously allows the void-free deposition of copper in cavities with particularly high shape factors, for example shape factors of more than 2:1, more than 3:1, more than 4:1, more than 5:1, more than 6:1 or more than 7:1 and higher, preferably less than 20:1 or less than 15:1.

[0105] According to one particular embodiment, the pattern has an opening size of 5-45 nm and a shape factor of 3:1-10:1.

[0106] The patterned surface of the conductive material has three main zones: (1) the field shared by all cavities of the pattern, (2) each cavity with its sidewalls, and (3) the bottom.

[0107] During the deposition step, the surface of the cavity to be filled can be polarized either in galvanostatic mode (fixed applied current), or potentiostatic mode (potential is applied and fixed, optionally relative to a reference electrode), or in pulse mode (current or voltage), or in ramp mode (current or voltage).

[0108] According to one embodiment of the present invention, the polarization of the surface of the cavities of the pattern is carried out in ramp mode applying voltages from the open circuit potential to -1.5 V / SCE (calomel saturated electrode) and from -1.5 V / SCE (calomel saturated electrode) to the open circuit potential, with a scan rate equal to 5 mV / s.

[0109] The electrolyte according to the invention may be used according to a procedure which includes an initial step of "hot entry", but particularly advantageously according to a procedure which includes an initial step of "cold entry", during which the surface to be coated is brought into contact with the electrodeposition bath without electric polarization and maintained in this state for the desired time. Thus, according to a particular feature, the method according to the invention includes, prior to electrodeposition, a step of "cold entry", during which the surface of the cavity to be filled is brought into contact with the electrodeposition composition according to the invention without electric polarization and optionally maintained in this state for at least 30 seconds.

[0110] The electrodeposition process according to the present invention can be carried out at room temperature, which may be between 20 and 35° C. Therefore, it is generally not necessary to heat the electrodeposition bath.

[0111] The method according to the invention provides copper deposits of excellent quality, for example free of material defects such as seams or voids.

[0112] Finally, the invention relates to a semiconductor device obtainable or obtained by the method just described.

[0113] The present invention will be described in more detail in the following examples, in which the temperature is room temperature unless otherwise specified.

[0114] Example 1 Comparison: Characterization of the accelerating effect of thiodiglycolic acid using electrochemical deposition of copper The effect of thiodiglycolic acid on copper deposition was characterized electrochemically using a composition containing copper(II) sulfate, 2,2′-bipyridine, imidazole, tetraethylammonium hydroxide, and tartaric acid according to the teachings of U.S. Pat. No. 10,883,185, the subject matter of which is incorporated herein by reference in its entirety.

[0115] Materials and equipment: substrate: The substrate used in this example is bulk pure cobalt with a thickness of 10 micrometers and a diameter of 5 mm.

[0116] Electrolyte solution: 6.05 mM 2,2'-bipyridine, 6.05 mM imidazole, and 6.05 mM CuSO 4 (H 2 O) 5 A first solution was prepared containing: 65.4 mM tartaric acid and 64.1 mM CuSO 4 (H 2 O) 5 The first solution and the second solution were mixed in a predetermined ratio, thiodiglycolic acid was added, and the pH was adjusted to obtain an electrolyte solution.

[0117] The concentration of 2,2'-bipyridine in the resulting solution was 5.44 mM, and the concentration of imidazole was 5.44 mM. 4 (H 2 O) 5 The concentration of tartrate was 6.54 mM. The concentration of thiodiglycolic acid was 25 ppm. The pH of the solution was adjusted with tetra-ethylammonium hydroxide to be equal to 9.2.

[0118] Cu 2+ To ignore the current transfer contribution of 0.1M K 2 SO 4 The salt carrier was added.

[0119] Device: In this example, the electrochemical deposition apparatus consisted of two parts: (1) a cell intended to contain the electrodeposition solution, equipped with a system for recirculating the fluids to control the hydrodynamics of the system, and (2) a rotating electrode equipped with a sample holder suitable for the size of the parts used (4 cm x 4 cm).

[0120] The electrodeposition cell had two electrodes: - Working electrode: Co rotating disk electrode (D=5mm) - Counter electrode: Platinum -Reference electrode: Calomel saturated electrode (CSE)

[0121] Connectors provided electrical contact between the electrodes which were connected by wires to a potentiostat supplying a maximum of 20V or 2A.

[0122] Electrical protocol: Cathodic polarization was performed from an open circuit potential to −1.5 V / ECS and from −1.5 V / ECS to an open circuit potential, the scan rate was 5 mV / s, and the duration of the electrodeposition step was sufficient to measure the current response to evaluate the deposition kinetics.

[0123] standard: To evaluate the accelerator effect of thiodiglycolic acid, a reference test was performed: The protocol above was reproduced except that the electrolyte solution did not contain thiodiglycolic acid.

[0124] Evaluation of accelerator effect A low current was observed during the first scan (from the open circuit potential to −1.5 V / SCE), but hysteresis was observed during the reverse scan (from −1.5 V / SCE to the open circuit potential) once the surface passivation of the bulk cobalt was destroyed.

[0125] Hysteresis was characterized by ΔE, which is the difference in potential at which deposition occurs when passivation is intact (forward scan) and degraded (reverse scan). The hysteresis surface area is a good indicator of the accelerator effect and can be extrapolated as a good indicator of the bottom-up effect of the accelerator during the electroplating deposition process on substrates etched with recessed features instead of flat bulk cobalt substrates. A high ΔE means that the accelerator thermodynamically facilitates copper reduction after passivation is broken down.

[0126] Results obtained: The ratio between the prior art (ΔE value of the electrolyte containing thiodiglycolic acid) and the reference (ΔE value of the electrolyte without the accelerator molecule) was found to be 1.1.

[0127] The same ratio was also measured using hysteresis surface area as the parameter.

[0128] Conclusion: Using thiodiglycolic acid as an accelerator and the standard, comparable ΔE and hysteresis surface areas were obtained, which means that thiodiglycolic acid has a very weak accelerator effect.

[0129] Example 2: Characterization of the accelerating effect of dithiodiglycolic acid using electrochemical deposition of copper Example 1 was reproduced, except that in the electrolyte solution, thiodiglycolic acid was replaced by dithiodiglycolic acid at various concentrations (i.e., 1-30 ppm). The best ΔE was obtained at a concentration of 10 ppm, resulting in a three-fold increase in ΔE and hysteresis surface area. This value is significantly higher than that obtained under similar conditions in Example 1, which means that dithiodiglycolic acid has a stronger accelerator effect than thiodiglycolic acid.

[0130] Example 3: Characterization of the accelerating effect of thioglycolic acid using electrochemical deposition of copper Example 1 was reproduced, except that thiodiglycolic acid was replaced with thioglycolic acid of various concentrations (e.g., 1-30 ppm) in the electrolyte solution. The highest ΔE was obtained at a concentration of 5 ppm, resulting in a 2.5-fold increase in ΔE and a 2.5-fold increase in hysteretic surface area.

[0131] This value is significantly higher than that obtained under similar conditions in Example 1, which means that thioglycolic acid has a stronger accelerator effect than thiodiglycolic acid.

[0132] Example 4 Comparison: Characterization of the thiourea acceleration effect using electrochemical deposition of copper Example 1 was reproduced except that thiodiglycolic acid was replaced with thiourea having concentrations between 0.2 and 2 ppm, with the highest ΔE obtained at a concentration of 1 ppm, resulting in a 1.5-fold increase in ΔE and hysteresis surface area based on the baseline.

[0133] Example 5: Characterization of the accelerating effect of ammonium thiocyanate using electrochemical deposition of copper Example 1 was reproduced except that thiodiglycolic acid was replaced with ammonium thiocyanate at a concentration of less than 1 ppm, resulting in the highest ΔE at a concentration of 0.5 ppm.

[0134] In this case, the ΔE and hysteresis surface area increased by a factor of 2.0 based on the baseline.

[0135] The results of Examples 1-5 are summarized below in Table 1. The concentration of each accelerator is varied since stability and ΔE vary with concentration.

[0136] [Table 1]

[0137] The examples demonstrate that the use of one of the accelerators in a copper electrolyte produces copper deposits that are free of voids, seams, and other defects.

Claims

1. An electrolyte having a pH of 8.5 to 9.5 for the electrodeposition of copper onto a conductive substrate, said electrolyte comprising, in aqueous solution, - 0.4 to 50 mM copper (II) ions; - 0.4 to 50 mM of a mixture consisting of a first aromatic amine, a second aromatic amine, and a complexing agent for copper(II) ions; at least one accelerator selected from the group consisting of dithiodiglycolic acid, thioglycolic acid, thiourea, ammonium thiocyanate, thiocyanic acid, and combinations thereof; Electrolytes, including:

2. 2. The electrolyte of claim 1, wherein the first aromatic amine is 2,2'-bipyridine and the second aromatic amine is imidazole.

3. 3. The electrolyte of claim 2, wherein the ratio between the molar concentration of 2,2'-bipyridine and the molar concentration of imidazole is from 1:2 to 2:

1.

4. 4. An electrolyte according to any one of claims 1 to 3, wherein the complexing agent for the copper(II) ions is tartrate or ethylenediamine.

5. 5. The electrolyte according to claim 1, wherein the molar ratio between the concentration of the first amine and the concentration of the complexing agent is from 1 / 4 to 4 / 1, such as from 1 / 3 to 3 / 1, or from 1 / 2 to 2 / 1 ±10%.

6. Electrolyte according to any one of the preceding claims, wherein the concentration of said at least one accelerator is between 0.05 ppm and 200 ppm, preferably between 0.1 ppm and 20 ppm.

7. 7. The electrolyte of claim 6, wherein the accelerator is dithiodiglycolic acid and is present at a concentration of 5 ppm to 15 ppm.

8. The electrolyte of claim 6, wherein the accelerator is thioglycolic acid and is present at a concentration of 1 ppm to 10 ppm.

9. The electrolyte of claim 6, wherein the accelerator is thiourea and is present at a concentration of 0.1 ppm to 2 ppm.

10. 7. The electrolyte of claim 6, wherein the accelerator is ammonium thiocyanate and is present at a concentration of 0.1 ppm to 2 ppm.

11. 1. A process for electrochemical copper deposition onto a substrate comprising at least one exposed conductive surface, comprising: - contacting said exposed conductive surface with an electrolyte according to any one of claims 1 to 10; - polarizing said exposed conductive surface with a cathodic current to allow electrodeposition of copper onto said exposed conductive surface for a time sufficient to form a copper deposit; The process includes:

12. 12. The electrochemical process of claim 11, wherein the conductive exposed surface is a surface of a material consisting essentially of cobalt, copper, or ruthenium.

13. The electrochemical process of claim 12, wherein the material is in the form of a layer having a thickness of from 1 nm to 10 nm.

14. 12. The electrochemical process of claim 11, wherein the exposed conductive surface is a surface of a pattern cut into a dielectric substrate.

15. 15. The electrochemical process of claim 14, wherein the polarization of the exposed conductive surface is carried out for a time sufficient to completely fill the pattern with a void-free copper deposit.

16. Electrochemical process according to claim 14 or 15, wherein the pattern has an opening size of 5-45 nm and a shape factor of greater than 2, preferably 3-10, more preferably 4-10.

Citation Information

Patent Citations

  • Steel member acidic electroplating additive for copper pre-plating and pre-plating process

    CN101302635A

  • Copper electrodeposition solution and process for high aspect ratio patterns.

    JP2020503459A